2019
DOI: 10.1021/acs.chemmater.9b03031
|View full text |Cite
|
Sign up to set email alerts
|

Design of Phosphorene for Hydrogen Evolution Performance Comparable to Platinum

Abstract: Phosphorene, a monolayer of bulk black phosphorus, is promising for light harvest owing to its high charge mobility and tunable direct band gap covering a broad spectral range of light. Here, via atomic-scale first-principles simulations, we report a ultrahigh activity of hydrogen evolution reaction (HER) of phosphorene originated from defective activation. Quantitative evaluation of the Gibbs free energy of the ad/desorption of hydrogen (H*) to/from phosphorene (∆GH*) reveals that atomic vacancies and edges p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 59 publications
(125 reference statements)
0
61
0
Order By: Relevance
“…Cai and co‐workers first attempted to reveal the catalytic mechanism of phosphorene from the atomic standpoint, and they believed that the perfect phosphorene could be catalytically inert for HER. [ 54 ] Indeed, the inert HER activity of perfect phosphorene is mainly ascribed to the high H* adsorption energy associated with the packed lone‐pair p electrons of phosphorus atoms. Therefore, modulation in the electronic structure of phosphorene is desired.…”
Section: Black Phosphorusmentioning
confidence: 99%
See 1 more Smart Citation
“…Cai and co‐workers first attempted to reveal the catalytic mechanism of phosphorene from the atomic standpoint, and they believed that the perfect phosphorene could be catalytically inert for HER. [ 54 ] Indeed, the inert HER activity of perfect phosphorene is mainly ascribed to the high H* adsorption energy associated with the packed lone‐pair p electrons of phosphorus atoms. Therefore, modulation in the electronic structure of phosphorene is desired.…”
Section: Black Phosphorusmentioning
confidence: 99%
“…Despite atomic sites at di‐vacancies are catalytically inert, a proper tensile strain caused by the locally distorted lattice sites in the defect cores can make it catalytically active. [ 54 ] In addition to the vacancies and strains, the edges and metal doping were considered in the DFT calculation and showed to potentially boost the HER activity. Lu and co‐workers indicated that the exposed edges could introduce more active sites and present higher electrochemical activity compared to the basal plane due to the metallic character of edges.…”
Section: Black Phosphorusmentioning
confidence: 99%
“…274 Phosphorene based on its inherent properties displays a wide light absorption range from ultraviolet to near-infrared View Article Online making it very appealing for solar photocatalysis applications. [275][276][277][278][279] However, it is considerably less stable than graphene, with a tendency to oxidize towards P x O y . The oxidative degradation of the material in ambient conditions is still a puzzling obstacle towards practical applications.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%
“…[60] A very recently research via DFT calculations reported that the HER activity of BP originated from defects and the reaction could be activated by atomic vacancies and edges based on the quantitative evaluation of the Gibbs free energy of the ad/desorption of hydrogen (H*) to/ from phosphorene (ΔG H* ). [61] The corresponding electrocatalysts mentioned in the whole section 2 have been tabulated and are listed in Table 1. The Pt/C catalyst is presented as a reference.…”
Section: Bp-based Materials For Hermentioning
confidence: 99%
“…Theoretical calculations showed that both heteroatoms doping and functional groups introducing could effectively enhance the HER catalytic performance of the plane and zigzag edge of BP, but degrade the catalytic activity of armchair edge slightly . A very recently research via DFT calculations reported that the HER activity of BP originated from defects and the reaction could be activated by atomic vacancies and edges based on the quantitative evaluation of the Gibbs free energy of the ad/desorption of hydrogen (H*) to/from phosphorene (ΔG H* ) . The corresponding electrocatalysts mentioned in the whole section 2 have been tabulated and are listed in Table .…”
Section: Bp Based Electrocatalysts For Hermentioning
confidence: 99%